Intensive Circuit Class Therapy in Patients with Relapsing-Remitting Multiple Sclerosis - Kocica, Jan; Kolcava, Jan; Sladeckova, Michaela; Stourac, Pavel; Vlckova, Eva; Dosbaba, Filip; Kratochvilova, Jitka; Bednarik, Josef (Journal of rehabilitation medicine, 2022)
OBJECTIVE: Long-term physiotherapy is of considerable benefit to patients with multiple sclerosis (MS) who have motor dysfunction or gait impairment. The aim of this study was to determine the effectiveness of a 12-week intensive circuit class therapy for patients with MS, with a wider focus on fatigue and gait ability. METHODS: A total of 46 patients with relapsing-remitting MS were divided randomly into 2 groups: 23 patients (mean Expanded Disability Status Scale (EDSS) 2.33 ± 0.74) participated in an intensive 12-week course of intensive circuit class therapy, and 23 patients (mean EDSS 2.04 ± 0.63) served as a control group. The EDSS, Timed Up and Go (TUG) test and Four-Stage Balance Test (FSBT) made up the physical testing part, supplemented by questionnaires such as the Modified Fatigue Impact Scale (MFIS), 12-Item Multiple Sclerosis Walking Scale (MSWS-12), Beck Depression Inventory (BDI) and 36-Item Short Form Survey (SF-36). RESULTS: Significant improvements were found among intensive circuit class therapy-exercising patients in FSBT (p < 0.05), TUG test (p < 0.01), MFIS (p < 0.01), BDI (p < 0.05), MSWS-12 (p < 0.05) and the 3 subscales of SF-36 after 12 weeks of intensive circuit class therapy, while there were no significant changes in the control group. CONCLUSION: Intensive circuit class therapy is an effective therapeutic approach for improving gait and balance problems in patients with MS. It has also proved to alleviate fatigue and symptoms of depression.
Keywords: terapie cvičením; relabující-remitující roztroušená skleróza; lidé; Fatigue; Exercise Therapy; chůze (způsob); Multiple Sclerosis, Relapsing-Remitting; Treatment Outcome; Gait; výsledek terapie; únava; Humans